2023
DOI: 10.1186/s13059-023-03001-z
|View full text |Cite
|
Sign up to set email alerts
|

Predicting disease severity in metachromatic leukodystrophy using protein activity and a patient phenotype matrix

Abstract: Background Metachromatic leukodystrophy (MLD) is a lysosomal storage disorder caused by mutations in the arylsulfatase A gene (ARSA) and categorized into three subtypes according to age of onset. The functional effect of most ARSA mutants remains unknown; better understanding of the genotype–phenotype relationship is required to support newborn screening (NBS) and guide treatment. Results We collected a patient data set from the literature that rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 81 publications
1
4
0
Order By: Relevance
“…As we await the final evaluation results by the CAGI6 assessors, it is noteworthy that the QAFI versions show Pearson correlations with the experimental results. (Trinidad et al 2023) that are within the high range observed for our method (Supplementary Table S5).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…As we await the final evaluation results by the CAGI6 assessors, it is noteworthy that the QAFI versions show Pearson correlations with the experimental results. (Trinidad et al 2023) that are within the high range observed for our method (Supplementary Table S5).…”
Section: Discussionsupporting
confidence: 78%
“…1B) designed to improve the quantitative prediction of the functional impact of missense variants, an important goal in the evolution of in silico pathogenicity predictors (Masica and Karchin 2016;Diaz et al 2023) that clears the way for novel applications. For example, continuous scores can serve to predict disease severity in some diseases, like in the case of ARSA (Trinidad et al 2023) where it has fueled the corresponding CAGI6 challenge. They can also contribute to build more realistic fitness models in evolutionary studies, a field where in many cases only free energy estimates are employed (Echave and Wilke 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity and specificity of such studies are still under investigation. However, due to the genetic heterogeneity inherent in MLD and the presence of numerous rare and/or private variants especially in non-Caucasian groups, genetic screening has the risk of being less sensitive than biochemical screening methods [60].…”
Section: Genetic Screeningmentioning
confidence: 99%
“…Almost all MLD cases are caused by biallelic variants in ARSA ; cases caused by variants in PSAP are extremely rare [ 6 , 7 ]. The MLD field is rapidly evolving due to new innovations, such as the recently authorized ex vivo gene therapy in the European Union for LI and EJ MLD [ 8 ] and development of emerging guidelines and newborn screening programs [ 9 , 10 ]. Gene therapy is not yet universally accessible nor approved in late-onset MLD.…”
Section: Introductionmentioning
confidence: 99%